Enablers for the Success for Competitive Stance in Portuguese Companies Due to Digital Transformation During Covid-19 - Moreira, Fernando (2023)
The rapid development of digital technologies has dramatically affected organizations across a wide range of business sectors. Companies that rely on/use such technologies and transform a significant part of their modus operandi, including operational and management, thus achieve digital transformation (DT), and their market value typically increases. Digital technologies—also called innovation accelerators—include, among many others, the Internet of Things (IoT), Big Data analytics, and Artificial Intelligence (AI). In this circumstance, the main goals of this research are to understand how organizations are changing, what causes the change, and how different organizations work in practice “against” each other in the context of digital transformation. The research presented here involved 8183 companies, registered in the AICEP database of Portuguese companies, resulting in a sample of 93 with valid responses belonging to various sectors of activity. The statistical analysis used to identify the items that made up six defined dimensions: (1) Strategic Vision, (2) Culture of Innovation, (3) Know-how and Intellectual Property, (4) Digital Capabilities, (5) Strategic Alignment and (6) Technology assets was Exploratory Factor Analysis (EFA). The six dimensions make it easier to compare one business to others, even whether they are in similar stages of growth in terms of DT or within the same activity sector. The research demonstrates that to participate in DT inside an organization, various hard and soft skills are needed for the distinct aspects of the process. The findings suggest the high level of diversity and the necessity for a comprehensive strategy to handle businesses’ complexity, where leadership plays a crucial role. The research additionally shows how a variety of capabilities must be used to implement, evaluate, and monitor specific requirements in a particular environment to achieve DT.